Respiratory muscle strength no influence the need for noninvasive ventilation after heart surgery (Fisioterapia e Pesquisa, 2014)
The aim of this study was to investigate the relation between preoperative respiratory muscle strength and indication and performance of noninvasive ventilation in the planned heart surgery. We conducted a retrospective study using data collected from clinical records and analyzed 109 medical records and noninvasive ventilation accompanying paper. We analyzed the values of respiratory muscle strength, peak flow and respirometry, as well as the postoperative respiratory complications, correlating them with indication and performance of the noninvasive ventilation. The t test was performed for continuous variables; the chi-square was used to investigate the influence of preoperative respiratory muscle strength values in the indication of noninvasive ventilation. Noninvasive ventilation was used in 32 (29%) subjects and the prime motive indication was hipercapy (44%). The successful use of noninvasive ventilation was observed in 94%. The decrease in preoperative strength, despite having a lower performance, showed no significant difference in relation to its use and outcome (p=0.73). The preoperative respiratory muscle strength was not able to provide for the use of noninvasive ventilation or its performance.